The genome sequence of the club-tailed millipede, Cylindroiulus punctatus (Leach, 1816) [version 1; peer review: 2 approved] - Mark G. Telfer; Gregory D. Edgecombe; Liam M. Crowley (Wellcome Open Research)
We present a genome assembly from a female specimen of Cylindroiulus punctatus (club-tailed millipede; Arthropoda; Diplopoda; Julida; Julidae). The genome sequence has a total length of 354.09 megabases. Most of the assembly (92.9%) is scaffolded into 7 chromosomal pseudomolecules. The mitochondrial genome has also been assembled, with a length of 18.98 kilobases.